Just living : poems and prose by the Japanese monk Tonna - Ton'a, 1289?-1372?; Carter, Steven D. (New York : Columbia University Press, 2003)
One of the best scholar-translators in the field presents a selection of writings by Tonna (1289--1372), an outstanding medieval Buddhist poet-monk, very little of whose work has been translated until now. Tonna was regarded as the leading Nijo ̄ poet of his day and was known as one of the Four Deva Kings of the Waka. This anthology contains translations of 134 uta, 16 linked-verse couplets, and selections from a prose narrative, From a Frog at the Bottom of a Well, along with an introduction and explanatory notes, a glossary of important names and places, and a list of sources.
Cover; Half title; Title; Copyright; Dedication; Contents; Acknowledgments; Introduction; The Poems; From a Frog at the Bottom of a Well : Selections; Glossary of Important Names and Places; Sources of the Poems; Index of First Lines; Series List.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Ton'a, -- 1289?-1372? -- Translations into English; Ton'a, -- 1289?-1372?; LITERARY CRITICISM -- Asian -- General; LITERARY COLLECTIONS -- Asian -- General; Electronic books; poetry; Translations; Vertalingen (vorm); Gedichten (teksten); Poetry; Poésie.